Field Bio-Efficacy of Newer Insecticides against Eggplant Fruit and Shoot Borer, Leucinodes orbonalis Guenee - Mainali, Ram Prasad; Peneru, Ram Babu; Pokhrel, Padma; Giri, Yagya Prasad (International Journal of Applied Sciences and Biotechnology, 2015)
Eggplant fruit and shoot borer (EFSB), Leucinodes orbonalis Guenee (Lepidoptera: Pyralidae) is a key insect pest of eggplant in all eggplant growing areas of Nepal. A field experiment was carried out in Khumaltar, Lalitpur during summer season of 2014 using eight treatments as, i) Abamectin 1.9 EC @ 1.5 ml/lit; ii) Spinosad 45 SL @ 0.25 ml/lit; iii) Emamectin Benzoate 5 SG @ 0.3 gm/lit; iv) Tozen @ 0.33 ml/lit; v) Karanjin 2 EC @ 2ml/lit; vi) Borer Gourd (Bacillus thuringiensis var. Kurstaki 108 CFU/ml + Beauveria bassiana 108 CFU/ml + Verticillium lecanii 108 CFU/ml + Metarhizium anisopliae 108 CFU/ml) @ 2 ml/lit; vii) Chlorantraniliprole 18.5 EC @ 0.25 ml/lit and viii) Untreated check to test efficacy of newer bio-rational insecticides against L. orbonalis. The treatments were arranged in randomized complete block design (RCBD) with three replications. The result showed that the fruit infestation percent on number and weight basis was significantly the lowest in Chlorantraniliprole (6.57 and 6.31) and Spinosad (12.08 and 11.15) treated plots as compared to other treatments. The Chlorantraniliprole treated plot recorded the maximum marketable yield (32.03 mt/ha) followed by Spinosad (30.93 mt/ha) with 34.39 percent and 29.77 percent increase in marketable fruit yield over untreated check, respectively. Hence, the use of Chlorantraniliprole and Spinosad could be one of the better options for effective management of L. orbonalis.Int J Appl Sci Biotechnol, Vol 3(4): 727-730